ISLAMIC CAPITAL MARKET-GROWTH NEXUS PRE AND POST IFSA 2013: EMPIRICAL EVIDENCE FROM MALAYSIA - Kamarudin, Ainatul Aqilah; Duasa, Jarita; Kassim, Salina; Imon, Riasat Amin (International Journal of Islamic Banking and Finance Research, 2023)
This study examines the relationship between Islamic capital market and Malaysian real economic growth pre and post IFSA 2013 from 2007 to 2019. This study adopts both quantitative and qualitative analysis, where Autoregressive Distributed Lag (ARDL) method of cointegration is adopted for the quantitative analysis, while interview session is adopted for the qualitative analysis. The findings found that the link between Shari’ah-compliant Securities (SCS) and the real economic growth is negatively significant, while the link between Shari’ah-compliant Market Capitalization (SCMC) and the real economic growth is positively significant in both short and long runs. It is also shown that IFSA 2013 does assist the Islamic capital market sector to improve the real economic growth in Malaysia via its rules and regulations, as the coefficients and significance of the real economic growth as proxied by the industrial production index (IPI) are improving with the implementation of IFSA 2013. Besides, the qualitative results of the study have shown that Islamic capital market does promote economic growth by ensuring stability in the market and significantly contributing to the environmental, social and governance (ESG) via the implementation of SRI Sukuk, Bond Grant Scheme, ESG Financing/Sukuk, and value-based judgement projects. The work gives some insights into the field of Islamic capital market-growth nexus from the perspective of a developing country, which is Malaysia. It also delves further into the Islamic capital market-growth nexus by considering the effect of IFSA 2013. JEL Classification Codes: E44, E58, E60, O00.